A new approach to application of the method of measuring electric field strength by average value - L. V. Tyukina; S. V. Biryukov; A. V. Tyukin (Омский научный вестник)
The paper considers a new possibility of using the method of measuring the electric field strength by an average value in order to reduce the error from the inhomogeneity of the field and expand the spatial range of measurements. The studies carried out in the work allowed us to establish that when using the measurement method by the average value, there are always three values at each measurement step, two of which correspond to the two previous values of the EP intensity determined with errors opposite in sign, and the third corresponds to the average value of them. Therefore, in the work, it is proposed to measure the electric field strength at one point in space by two sensors with errors opposite in sign. At the same time, alternately determining at each step of averaging the average value of the EP intensity from the previously obtained and subsequent average values, bringing the measurement result closer to the true value. Based on the results of theoretical research, a new method is proposed — the "Measurement method with step-by-step averaging", which, without complicating the measurement process, makes it possible to reduce by two to three times the error in measuring the intensity of inhomogeneous electric fields in a wide spatial range compared with the measurement method by the average value.